2022
DOI: 10.1039/d2ta00504b
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide reduction reaction for efficient ammonia synthesis on topological nodal-line semimetal Cu2Si monolayer

Abstract: It is imperative to remove NO from exhausted gas, and electrochemical NH3 synthesis via N2 reduction still suffers from the low activity and low selectivity. It is of interest that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 66 publications
0
23
0
1
Order By: Relevance
“…It is worth noting that the crystal orbital Hamilton population (COHP) and the integrated COHP (ICOHP) have been shown to be effective and sensitive indicators that can characterize the degree of NO activation. , For the Co@MoS 2 (Figure d), Y@MoS 2 , and Hf@MoS 2 (Figure S3a,b) catalysts, after the NO adsorption, the COHP of *NO has more antibonding states than that of the free NO molecule. Furthermore, the corresponding ICOHP values of the adsorbed *NO (N–O) over these three catalysts are −18.31, −18.79, and −18.59, which are less negative than that of free NO (ICOHP = −19.31).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that the crystal orbital Hamilton population (COHP) and the integrated COHP (ICOHP) have been shown to be effective and sensitive indicators that can characterize the degree of NO activation. , For the Co@MoS 2 (Figure d), Y@MoS 2 , and Hf@MoS 2 (Figure S3a,b) catalysts, after the NO adsorption, the COHP of *NO has more antibonding states than that of the free NO molecule. Furthermore, the corresponding ICOHP values of the adsorbed *NO (N–O) over these three catalysts are −18.31, −18.79, and −18.59, which are less negative than that of free NO (ICOHP = −19.31).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the crystal orbital Hamilton population (COHP) and the integrated COHP (ICOHP) have been shown to be effective and sensitive indicators that can characterize the degree of NO activation. 36,44 For the Co@ The limiting potential (U L ) is the best activity descriptor for electrocatalysts, which is the required applied potential to make every elementary step exergonic (ΔG < 0). 42,53 Let us first discuss U L of those catalysts that favor NH 3 .…”
Section: No Adsorption and Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum catalysis theory is a novel catalyst design theory developed in the last decade, which has been validated by several comparisons of theorical and experimental results. Chen et al proposed for the first time that the surface states of a topological insulator can diffuse to surface-supported Au clusters to promote CO oxidation . Later, it was found that a few classified topological semimetallic materials can also be used as catalysts for certain reactions, such as the Weyl semimetals (WSMs) NbAs and TaAs for simple molecule activation reactions and the topological nodal line semimetals (TNLSMs) ZrSiS and ZrSiSe for the HER .…”
Section: Introductionmentioning
confidence: 99%
“…Nitrate (NO 3 – ) is one of the main pollutants in wastewater, and it usually arises from the excess use of fertilizers or from smelting and pharmaceutical processes. , The increasing contamination of nitrate can lead to water acidification and lower concentration of dissolved oxygen, thus reducing the amount of aquatic organisms as well as increasing the level of toxicity which can induce cancer. On the other hand, the strong oxidizing property, low dissociation energy of the nitrogen–oxygen bond and the high solubility of NO x species , could favor the production of value-added ammonia under electrochemical conditions. The electrochemical NRA route involves the transfer of nine protons and eight electrons in different pathways, , which can be described as follows: normalN O 3 + 9 normalH + + 8 normale normalN normalH 3 + 3 normalH 2 normalO …”
mentioning
confidence: 99%